Influence of heavy haul railway curve parameters on rail wear. (November 2015) - Wang, Jianxi; Chen, Xi; Li, Xiangguo; Wu, Yanjie
Abstract: With the use of virtual prototype technology, a heavy haul vehicle-track dynamic model was established and the influence of curve parameters (including curve radius, circular curve length and transition curve length) and track parameters (including superelevation and rail cant) on rail wear was researched. The measures to reduce wear from optimizing curve parameters were summed up, by means of the analysis to the comparisons of a variety of parameter combinations. The study results prove that: when the curve radius is less than 800 m, the curve radius has a great influence on rail wear and the length of transition curve does too. When the curve radius is around 600 m (which means that the curve is a small radius curve), increasing the rail cant of the inner rail to 1/20 will effectively reduce the wear of the curve rail, and setting the inadequate superelevation to around 20% less than the balanced superelevation will, too. When the curve radius is around 800 m, increasing the rail cant of the inner rail to 1/20 will effectively reduce the wear of the curve rail, and setting the inadequate superelevation to around 10% to 15% less than the balanced superelevation will, too. When the curve radius is greater than 1000 m, only increasing the rail cant of the inner rail to 1/20 can effectively reduce the wear of the curve rail. Highlights: When the curve radius is less than 800 m, it has a great influence on rail wear. When the curve radius is less than 800 m, the length of easement curve affects rail wear greatly. In order to reduce rail wear, rail cant and superelevation allocation methods are also different under different curve radii.